2020
DOI: 10.1071/wr19153
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefits and short-term costs: small vertebrate responses to predator exclusion and native mammal reintroductions in south-western New South Wales, Australia

Abstract: ContextThe success of conservation fences at protecting reintroduced populations of threatened mammals from introduced predators has prompted an increase in the number and extent of fenced exclosures. Excluding introduced species from within conservation fences could also benefit components of insitu faunal assemblages that are prey for introduced predators, such as reptiles and small mammals. Conversely, reintroduced mammals may compete with smaller mammals and reptiles for resources, or even prey on them. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…For range-resident feral cats, the observed extended home range (AKDE95) was about double the size of home ranges estimated for feral cats in another arid region of Western Australia (Wysong et al 2020), about three times that estimated for arid South Australia (Moseby et al 2009), and four times that estimated for subtropical savannas in northern Australia (McGregor et al 2015). This suggests that prey resources are more limiting in the semiarid woodland environments of our study area compared to regions with greater rainfall and/or more diverse reptile and small mammal faunas, for instance, rodents (see Roshier et al 2020). The near-constant movement by non-sedentary feral cats observed in this study has been observed in previous studies in semiarid or arid environments and has been attributed to nutritional stress (Jones and Coman 1982, Edwards et al 2001, Moseby et al 2009.…”
Section: Home-range Estimation and Overlapsupporting
confidence: 71%
See 2 more Smart Citations
“…For range-resident feral cats, the observed extended home range (AKDE95) was about double the size of home ranges estimated for feral cats in another arid region of Western Australia (Wysong et al 2020), about three times that estimated for arid South Australia (Moseby et al 2009), and four times that estimated for subtropical savannas in northern Australia (McGregor et al 2015). This suggests that prey resources are more limiting in the semiarid woodland environments of our study area compared to regions with greater rainfall and/or more diverse reptile and small mammal faunas, for instance, rodents (see Roshier et al 2020). The near-constant movement by non-sedentary feral cats observed in this study has been observed in previous studies in semiarid or arid environments and has been attributed to nutritional stress (Jones and Coman 1982, Edwards et al 2001, Moseby et al 2009.…”
Section: Home-range Estimation and Overlapsupporting
confidence: 71%
“…Approximately 8000 ha of the sanctuary is surrounded by an electrified conservation fence, within which foxes and cats have been excluded since 2007, and five threatened mammals have been reintroduced successfully (Roshier et al. 2020). A combination of poison baits and Canid Pest Ejectors is used to suppress foxes in a 36,000‐ha area to the south of the conservation fence at Scotia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2009, 2018; Hutchison 2013; Fulton 2017; Roshier et al . 2020), levels of seed predation (Murphy et al . 2005; Mills et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cat-free islands and fenced areas have prevented the extinction of eight Australian mammal species, and further expansion should extend protection to other species that are highly susceptible to cat predation (Legge et al 2018). The ark network has focussed on threatened mammals and birds (especially on islands), but Roshier et al (2020) describe the effects of a large mainland fenced area on other species, showing that small mammals benefited from the exclusion of feral animals, but small reptiles did not, possibly because the reintroduced mammals competed with resources important to the reptiles, or preyed on the reptiles directly.…”
Section: Controlling Cat Populationsmentioning
confidence: 99%